The Hemodynamic Management and Postoperative Outcomes After Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy: A Prospective Observational Study - Sohan Lal Solanki; Vandana Agarwal; Reshma P. Ambulkar; Malini P. Joshi; Shreyas Chawathey; Shivacharan Patel Rudrappa; Manish Bhandare; Avanish P. Saklani (Critical Care Research and Practice)
Conclusion: A higher PCI score was significantly associated with increased duration of surgery, fluid requirements, the need for invasive hemodynamic monitoring, postoperative complications, and longer ICU stays. Tailoring perioperative strategies based on PCI scores has the potential to optimize these outcomes.